Relationship between fluorescence excitation-emission matrix properties and the relative degree of DOM hydrophobicity in wastewater treatment effluents. (September 2020) - Xiao, Kang; Yu, Jinlan; Wang, Shu; Du, Jianqing; Tan, Jihua; Xue, Kai; Wang, Yanfen; Huang, Xia
Abstract: Excitation-emission matrix (EEM) fluorescence spectroscopy is a powerful tool for the characterization of dissolved organic matter (DOM) in wastewater systems. It is of particular value if its utility could be extended by connecting the spectral features to hydrophobicity, one of the fundamental physicochemical properties of DOM. In this study, we employed a DAX-8 resin column to fractionate the hydrophobic/philic components of DOM and determine the relative degree of hydrophobicity by adjusting the critical retention factor ( k' cr, the ratio of treated water sample volume to column volume). A higher k' cr would result in a higher hydrophobicity of the column effluent. At different k' cr values (5, 10, 25, 50, 100, and 200), the EEM characteristics of the obtained DOM components were inspected, including overall properties (average fluorescence per total organic carbon and UV absorbance), regional properties (fluorescence regional integration (FRI) and its secondary parameters), and energy-related properties (energy level of the excited states, Stokes shift for relaxation of the excited states, and fluorescence lifetime). In case studies of a wastewater membrane bioreactor and an oxidation ditch, plenty of the EEM properties varied significantly with log k' cr ( r  > 0.9, p  < 0.05). The average fluorescence per UV absorbance (reflecting quantum yield), fluorescence proportion at Stokes shift ≥ 1.1 μm −1, and some secondary FRI parameters presented the best linear fitting with log k' cr, suggesting a smooth variation of the π-conjugated structures with the relative degree of DOM hydrophobicity. This may help to further understand the relationship between EEM fingerprints and DOM hydrophobicity. Graphical abstract: Image 1 Highlights: Fluorescence EEM fingerprints vary with the relative degree of DOM hydrophobicity. Critical retention factor ( k' cr ) of DAX column regulates the relative hydrophobicity. A set of intensity, wavelength and energy parameters are explored from EEM spectra. Fluorescence quantum yield, excitation energy, and Stokes shift correlate with k' cr . Some EEM parameters exhibit good linear regression with log k' cr, with R 2  > 0.95.